Exploring types and functions slang words in television series season 4 - Yulia, Erin; Ningsih, Tri Wahyu Retno (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2024)
Slang is an ever-evolving form of language that includes new vocabulary in phrases with extended meanings, often associated with younger generations. This study aims to discover the types and functions of slang words applied in On My Block TV Series Season 4 based on Allan and Burridge’s theory, the characters in On My Block TV Series Season 4 use slang in their daily or informal contexts. In this study, the writer used descriptive qualitative methods and utilized Allan and Burridge’s (2006) theory of types and functions of slang words to analyse the data. The research results showed 105 slang words used in On My Block TV Series Season 4 and identified 5 types of slang words applied. There were 53 fresh and creative types, 23 flippant types, 6 imitative types, 14 acronym types, and 9 clipping types. The writer also collected 6 functions of slang words applied, which are 7 to addresses, 7 to humiliates, 7 to initiate relax conversations, 6 to form an intimate atmosphere, 4 to express impressions, and 7 to reveal angers. The function of slang words to show intimacy does not apply in this series. Fresh and creative slang types and to initiate relax conversation slang functions are used more often in On My Block TV Series Season 4.